Masked Face Recognition using deep learning models - Omer T. Hamajan; Abbas M. Ali (Zanco Journal of Pure and Applied Sciences, 2024)
Face recognition has become indispensable in our daily lives as a quick and painless technique of confirming our identities since in the era of wearing face masks the traditional face recognition system may not effectively recognize the concerned person as an important part of the face (mouth, nose, and chin) which makes a substantial contribution to the face recognition process are occluded and partially hidden. The objective of our research is to tackle the challenges of the partially occluded face with a mask by training our custom dataset using those powerful pre-trained deep learning models like YOLO and Mask R-CNN which have not been used before for this purpose and to compare which one is outperforming the better results. To this end, models like (YOLOv5, YOLOv7, YOLOv8, and Mask R-CNN) have been employed and trained on the created dataset to check the accuracy and robustness of the occluded face recognition process. In addition, an online dataset such as (mfr2) which contains celebrities, and politicians masked and unmasked faces after expansion with more images has been used. The experimental findings demonstrate that the proposed algorithms give an accurate result, we achieve an accuracy of 97.5% using YOLOv8s, an accuracy of 89.7% using YOLOv7, and an accuracy of 89% using YOLOv5x, while an accuracy of 94.5% using Mask R-CNN. The study concludes that YOLOv8s outperforms the other models in masked face recognition.